Modelling of Cryopumps for Space Electric Propulsion Usage - Andreas Neumann; Michaela Brchnelova (Aerospace, 2024)
Electric space propulsion is a technology that is used in a continuously increasing number of spacecrafts. The qualification of these propulsion systems has to run in ground-based test facilities which requires long testing times and powerful pumping systems. In these usually large test facilities, high pumping speeds are achieved with cryopumps. Cryopump operation is very expensive with respect to electrical energy and cooling water consumption. Therefore, being able to optimize pump shape, cold plate material, and pump placement in a chamber is beneficial. Pump design and tuned operating strategies can reduce costs and increase intervals between regeneration. Testing different pump configuration setups in a large facility is mostly prohibitive due to high costs and long testing times. Optimization via modelling is a better choice for design and also, later, for operation. Therefore, having a numerical model and proven guidelines at hand for optimization is very helpful. This paper describes a new model developed at DLR for the optimization of cryopump layout and operation. Model results are compared with cryopump operational and warm-up data. This validation is the basis for further optimization actions like multi-layer insulation layouts and pump cold plate upgrades, and helps in understanding and mitigating the detrimental effect of water condensates on the cryopump cold plates.